Atypical resting state functional connectivity in mild traumatic brain injury. Issue 8 (21st June 2021) - Amir, Joelle; Nair, Jay Kumar Raghavan; Del Carpio‐O'Donovan, Raquel; Ptito, Alain; Chen, Jen‐Kai; Chankowsky, Jeffrey; Tinawi, Simon; Lunkova, Ekaterina; Saluja, Rajeet Singh
Abstract: Objectives: This study aimed to investigate changes in three intrinsic functional connectivity networks (IFCNs; default mode network [DMN], salience network [SN], and task‐positive network [TPN]) in individuals who had sustained a mild traumatic brain injury (mTBI). Methods: Resting‐state functional magnetic resonance imaging (rs‐fMRI) data were acquired from 27 mTBI patients with persistent postconcussive symptoms, along with 26 age‐ and sex‐matched controls. These individuals were recruited from a Level‐1 trauma center, at least 3 months after a traumatic episode. IFCNs were established based on seed‐to‐voxel, region‐of‐interest (ROI) to ROI, and independent component analyses (ICA). Subsequently, we analyzed the relationship between functional connectivity and postconcussive symptoms. Results: Seed‐to‐voxel analysis of rs‐fMRI demonstrated decreased functional connectivity in the right lateral parietal lobe, part of the DMN, and increased functional connectivity in the supramarginal gyrus, part of the SN. Our TPN showed both hypo‐ and hyperconnectivity dependent on seed location. Within network hypoconnectivity was observed in the visual network also using group comparison. Using an ICA, we identified altered network functional connectivity in regions within four IFCNs (sensorimotor, visual, DMN, and dorsal attentional). A significant negative correlation between dorsal attentional network connectivity and behavioral symptoms score was also found. Conclusions: Our findings indicate that rs‐fMRI may be of use clinically in order to assess disrupted functional connectivity among IFCNs in mTBI patients. Improved mTBI diagnostic and prognostic information could be especially relevant for athletes looking to safely return to play, as well for individuals from the general population with persistent postconcussive symptoms months after injury, who hope to resume activity. Abstract : We found extensive functional connectivity changes in a group of mild traumatic brain injury patients who were still experiencing post‐concussive symptoms months after injury. These results suggest that resting state fMRI may help improve diagnosis, prognosis and overall management of mild traumatic brain injury in athletes as well as in the general population suffering from this prevalent, yet commonly overlooked condition.